2016
DOI: 10.1111/anae.13504
|View full text |Cite
|
Sign up to set email alerts
|

A randomised placebo-controlled trial examining the effect on hand supination after the addition of a suprascapular nerve block to infraclavicular brachial plexus blockade

Abstract: Some surgeons believe that infraclavicular brachial plexus blocks tends to result in supination of the hand/forearm, which may make surgical access to the dorsum of the hand more difficult. We hypothesised that this supination may be reduced by the addition of a suprascapular nerve block. In a double-blind, randomised, placebo-controlled study, our primary outcome measure was the amount of supination (as assessed by wrist angulation) 30 min after infraclavicular brachial plexus block, with (suprascapular group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This clinical problem has recently received considerable attention, with several calls to seek alternatives to interscalene block in shoulder arthroscopy [ 9 ]. So, the need for a safer ISB alternative has prompted researchers to examine several options, including but not limited to the suprascapular block [ 14 ]. The suprascapular nerve block (SSNB) technique is a simple, easily reproducible technique that is thought to supply sensory fibers to approximately 70% of the shoulder joint and directly innervates the supraspinatus and infraspinatus muscles.…”
Section: Introductionmentioning
confidence: 99%
“…This clinical problem has recently received considerable attention, with several calls to seek alternatives to interscalene block in shoulder arthroscopy [ 9 ]. So, the need for a safer ISB alternative has prompted researchers to examine several options, including but not limited to the suprascapular block [ 14 ]. The suprascapular nerve block (SSNB) technique is a simple, easily reproducible technique that is thought to supply sensory fibers to approximately 70% of the shoulder joint and directly innervates the supraspinatus and infraspinatus muscles.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study that used surface electromyography to quantify the block of individual nerves after an infraclavicular brachial plexus block. Several studies have reported the effect of an infraclavicular brachial plexus block on the axillary nerve using different variations of simple sensory and motor tests, but only as secondary outcomes and results are conflicting, with rates ranging from 9% to 100% .…”
Section: Discussionmentioning
confidence: 99%
“…These data are corroborated by former studies where our infraclavicular method has been used. 3,4 Considering shoulder patients and the search for distal alternatives to interscalene block, we think that the results of the 3 studies support the idea of using infraclavicular blocks also to anesthetize the axillary nerve.…”
mentioning
confidence: 85%